The clinical and pathological features of Kimura disease in pediatric patients - Liu, Lili; Zhang, Wen; Huang, Minjie; Li, Kaiji; Zhu, Li’ou; Ke, Liqin; Huang, Juan; Wu, Ying (Frontiers in Medicine, 2024)
Background: Kimura disease is characterized by inflammation with its underlying causes remaining uncertain. There is a lack of comprehensive and systematic researches on pathology of this condition in pediatric patients. Our objective is to study the clinical and pathological attributes of Kimura disease in pediatric patients and investigate the potential diagnostic significance of IgE in this context.Methods: Clinical and laboratory information, pathological characteristics, and follow-up data were correlated to examine the distinctive feature. Immunohistochemistry, acid-fast stain and molecular assay were employed to identify the presence of IgE and pathogens.We conducted an analysis of five cases of Kimura disease in pediatric patients at our hospital. The patients' ages ranged from 5 years and 7 months to 14 years and 2 months, with four (80%) being male. The most common site was the head and neck region, particularly the postauricular subcutaneous area. Eosinophilia was observed in four patients (80%), and two patients (40%) had elevated serum immunoglobulin E levels. Histopathological changes included eosinophilic infiltrates, follicular hyperplasia, and proliferation of postcapillary venules. Immunohistochemical results supported the reactive nature of the lymphoid process and IgE deposition in the follicle, while no specific pathogens were discovered by special stain. All patients underwent surgical excision, and none experienced recurrence in their original location.Children with Kimura disease show distinct eosinophilic and IgE alterations in both laboratory findings and pathological features. The application of immunohistochemical staining of IgE could serve as a promising marker for diagnosing Kimura disease.